Stabilisation of diaphyseal fractures of both bones forearm with limited contact dynamic compression or locked compression plate: comparison of clinical outcomes - Gill, S. P. S.; Mittal, Ankit; Raj, Manish; Singh, Pulkesh; Kumar, Sunil; Kumar, Dinesh (International Journal of Research in Orthopaedics, 2017)
Background: The inception of Locking Compression Plate (LCP) has revolutionized fracture management. With their dramatic success for articular fractures, there is a speculation that they might be more appropriate for diaphyseal fractures as well. Methods: In this randomized prospective cohort study, 56 patients with diaphyseal fractures involving both bones of forearm were segregated into two groups based on internal fixation with Limited contact dynamic compression plate (LC-DCP)(n=28) or with Locking compression plate (LCP)(n=26). Clinical and radiological parameters were studied and functional evaluation was done with Disabilities of arm, shoulder, and hand (DASH) score. Results: Andersons’ criteria was employed to categorize the functional results. The mean duration of surgery and time to union were discovered to be less in favor of LCP group although statistically insignificant. No significant differences in two groups with respect to the functional evaluation (range of movement, Andersons’ criteria and DASH score) and complications could be discerned. No incidence of refracture or synostosis was encountered in any of the group. Conclusions: Although LCP is an effective treatment alternative and may have a subtle edge over LC-DCP in the management of these fractures, their supremacy could not be certified. We deduce that surgical planning and expertise rather than the choice of implant are more pivotal for outstanding results.